Juliet’s Migrations in Alice Munro’s Runaway: Making and Losing Connections - Christine LORRE-JOHNSTON (E-REA)
This reading of Alice Munro’s Juliet trilogy, in Runaway (2004), proposes an analysis of the sequence of three stories as one that simultaneously establishes connections and undermines them. As a result, Juliet’s migrations, from one period of her life to another, from one part of Canada to another, from one story to the next, both lead to a build-up of experience that lends itself to interpretation, and to a questioning of the meaning to be attributed to that experience. This is achieved in various ways: through mythological interpretation (and counter-interpretation) of her life; through the choice of a trilogy, by contrast in particular with a dyad; through the very functioning of the trilogy as pictorial tryptich that allows the circulation and therefore the instability and liveliness of sensations; and through the changing meaning of words, that convey evolving emotions and ways of feeling. In these different ways, Munro once more reports acute feelings, while leaving the narrative open to interpretation.